Perancangan Dashboard Sistem Informasi Penjaminan Mutu Perguruan Tinggi dengan Metode Design Thinking - Rosyidi, Lukman; Wibowo, Edi; Tsabitah, Haura (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Quality assurance is a crucial foundation for universities to ensure quality, accountability, and sustainable governance. Digital transformation in higher education quality governance requires an efficient, informative, and easy-to-use system. This study aims to design a prototype dashboard for an Internal Quality Assurance Information System based on user needs using the Design Thinking approach with a case study of the Sekolah Tinggi Teknologi Terpadu Nurul Fikri. The research process involves five main stages: Empathize, Define, Ideate, Prototype, and Test. Data was collected through interviews with quality assurance unit personnel and analyzed to formulate visual solutions that address user needs. The dashboard prototype was tested using the User Experience Questionnaire (UEQ) method and yielded positive scores across all dimensions, particularly clarity and stimulation. These results indicate that the developed design is capable of providing an effective user experience in supporting the implementation of the internal quality assurance system.